Social Phobia and its Association with Academic Performance among Student of Kerman University of Medical Sciences Iran - Shahrzad Mazhari; Maryam Ekhlaspour; Nabi Banazadeh (Kerman University of Medical Sciences, 2014)
Background & Objective: Public speaking is a common academic activity Social phobia is associated with fear of public speaking which affects educational achievement However few researches have examined the prevalence of social phobia among university students in Iran The aim of this study was to evaluate the prevalence of social phobia among students of Kerman University of Medical Sciences Iran and its impact on their academic performance   Methods: Social Phobia Inventory (SPIN) Brief Version of Negative Evaluation Scale and a questionnaire assessing demographic characteristics and academic performance were applied to 700 randomly selected students from Kerman University of Medical Sciences   Results: The prevalence of social phobia among the university students was 406% Grade Point Average (GPA) was not significantly different between the students with social phobia comparing to students without social phobia Yet students with social phobia believed that fear of speaking in public had negative effects on their academic performance In this study only 41% of students with social phobia have been visited by psychiatrists   Conclusion: Preventive strategies are recommended to reduce the underrecognition and the adverse impact of social phobia on academic performance of university students